PEMETAAN KEBUTUHAN INFRASTRUKTUR JALAN PADA SENTRA PRODUKSI PERTANIAN DI KABUPATEN PASER - Lisa Astria Milasari (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2022)
The condition of the sector in Paser Regency is currently growing. Given the contribution of each field to the nominal value of GRDP, economic growth is influenced by the dominant sector, which is 11.52 percen of the total value of GRDP. Specifically for Paser Regency, the impact of infrastructure development is an increase in the added value of the sector and has an effect on increasing the allocation of infrastructure spending in Paser Regency. Therefore, at least the things that need to be done to develop these agricultural centers, namely the construction of locations and road infrastructure in the areas of agricultural production centers. Paser Regency is dominated by food crops sub-sector and plantation sub-sector. The agricultural land area of ​​Paser Regency is 1,090,380 hectares, which consists of 13,729 hectares of paddy fields and 1,076,651 hectares of non-rice fields. Meanwhile, the area of ​​non-agricultural land in Paser Regency is 69,934 hectares. The plantation sub-sector is dominated by oil palm plantations covering an area of ​​20,534 hectares in Tanjung Harapan District. Meanwhile, for cocoa rubber commodity as much as 8,382 hectares. The connectivity of road infrastructure needs with production centers is comprehensive, considering that most of the roads in Paser Regency are damaged.